Applications of gene modification technologies in the treatment of inherited diseases - Superson, Maciej; Szmyt, Katarzyna; Wilk-Trytko, Klaudia; Krasnoborska, Julia; Samojedny, Sylwia; Szymańska, Katarzyna; Walczak, Kamil (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: In last years gene modification technologies such as CRISPR/Cas9 has had a revolutionary impact on the treatment of inherited diseases. Technologies developed from bacterial defense mechanisms, has become a basic tools in scientific research and medical therapies. In our article we provided an overview of applications of gene modifications technologies, directly focusing on CRISPR/Cas9, in genetic disease treatment. State of Knowledge: New applications of CRISPR/Cas9 are still being explored. Treating inherited diseases such as cystic fibrosis, Duchenne muscular dystrophy, thalassemia, hemophilia, Huntington's disease, Crigler-Najjar syndrome, sickle cell anemia, Marfan syndrome, and phenylketonuria, is feasible with this novel technique. A comparative analysis with other gene editing methods highlights CRISPR/Cas9's efficacy, ease of use, and multiplexing capabilities. Summary: CRISPR/Cas9 is a groundbreaking technology with broad applications in genetic research and therapy. Its ease of use, cost-effectiveness, and ability to target multiple genes simultaneously position it as a preferred method. However, there are some challenges associated with precision issues and ethical considerations in human embryo gene editing. As CRISPR/Cas9 continues to evolve, responsible application and ethical considerations are important for maximizing its potential in treatment of genetic diseases.